Pattern of Head Injury and Associated Injuries in the Patients Presenting to Neurosurgical Emergency - Salman Raza, Yasir Shahzad; Shafiq- ur-Rahman; Ali Tassadaq; Nadeem Akhtar (Journal of Rawalpindi Medical College, 2018)
Background: To assess the pattern of head injury and associated injuries along with head injury presenting to neurosurgical emergency after sustaining injuries by different modes.